Efficacy of Multiple- or Single-Dose Cidofovir against Vaccinia and Cowpox Virus Infections in Mice - Quenelle, Debra C. (American Society for Microbiology, 2003)
Orthopoxviruses, including variola and monkeypox, pose risks to human health through natural transmission or potential bioterrorist activities. Since vaccination has not recently been utilized for control of these infections, there is renewed effort in the development of antiviral agents not only for postexposure smallpox therapy but also for treatment of adverse reactions following vaccination. The objectives of this study were to expand on the results of others that cidofovir (CDV) is effective in mice inoculated with cowpox virus (CV) or vaccinia virus (VV) and to document the efficacy of single and interval dosing beginning prior to or after infection, particularly including evaluations using suboptimal doses of CDV. We utilized BALB/c or SCID mice inoculated with CV or VV as models for systemic poxvirus infections. BALB/c mice were inoculated intranasally with CV or VV and treated with CDV prior to or after virus inoculation. CDV, at concentrations as low as 0.7 to 6.7 mg/kg of body weight/day for 5 days, conferred significant protection when treatment was initiated as late as 72 to 96 h postinfection. A single-dose pretreatment or posttreatment with CDV at 3 to 100 mg/kg was effective when given as early as 5 days prior to infection or as late as 3 days after infection with either VV or CV. Interval treatments given every third day beginning 72 h postinfection using 6.7 or 2 mg of CDV/kg also proved effective against CV infections. When SCID mice were inoculated intraperitoneally with CV or VV and treated for 7 to 30 days with CDV, all the mice eventually died during or after cessation of treatment; however, significant delays in time to death and reduction of virus replication in organs occurred in most treated groups, and no resistance to CDV was detected.